حماية الأسرى في القانون الدولي الإنساني والشريعة الإسلامية - الرتمي عبد الحفيظ (Universty Of El-oued جامعة الوادي, 2024)
يعتبر موضوع حماية الأسرى في القانون الدّولي الإنساني والشّريعة الإسلامية، من الموضوعات ذات الصّلة بالمشاكل والنّتائج المترتبة على الأشخاص في الحروب والنّزاعات المسلحة الدّولية، حين وقوع الأسرى في قبضة الطّرف المعادي، والذي يسعى فيه كل طرف إلى إضعاف القدرة القتالية لدى الطّرف الخصم، وبغرض ضمان حماية الأسرى يقتضي تمييزهم عن بقية المحتجزين؛ وذلك بتحديد الشّروط الشّخصية والموضوعية والإجرائية التي تكفل لهم حقوقهم، والعمل على حمايتهم العامة والخاصة، بدءًا من تاريخ وقوعهم في الأسر إلى غاية إطلاق سراحهم وعودتهم إلى أوطانهم؛ والحرص على احترام شخصيتهم وكرامتهم ومعاملتهم بإنسانية وعدم اعتبارهم أهداف عسكرية، وتجنيبهم أن ترتكب ضدهم أو من قبلهم، الانتهاكات الجسيمة والخطيرة، التي يترتب عليها المسؤولية المدنية للدّولة الحاجزة، والمسؤولية الجنائية الفردية لمقترفيها؛ ولتكريس هذه الحماية يقتضي تفعيل الآليات الإنسانية والقضائية؛ الوقائية والرّدعية، التي تسهر على تطبيق هذه الحماية تحت إشرافها ومراقبتها. The issue of protecting prisoners of war in international humanitarian law and Islamic law is considered one of the issues related to the problems and consequences of people in wars and international armed conflicts, when prisoners fall into the grip of the hostile party, in which each party seeks to weaken the fighting capacity of the opposing party, and for the purpose of ensuring protection Prisoners must be distinguished from the rest of the detainees; By defining the personal, substantive and procedural conditions that guarantee their rights, and working to protect them publicly and privately, starting from the date of their capture until their release and their return to their homelands; To ensure respect for their personality and dignity, to treat them humanely, not to consider them military targets, and to spare them from committing grave and serious violations against or by them, which entail the civil responsibility of the Detaining Power, and the individual criminal responsibility of its perpetrators; To perpetuate this protection requires the activation of humanitarian and judicial mechanisms. Preventive and deterrent, which ensures the implementation of this protection under its supervision and control.
أطروحة دكتوراه تخصص قانون عام في الحقوق و العلوم السياسية
Keywords: الأسرى، الحماية، القانون، الشريعة، الحقوق، الإنسانية، الآليات.; Prisoners; Protection; Law; Sharia; Rights; Humanity; Mechanisms